2005
DOI: 10.1111/j.1525-1497.2005.0087.x
|View full text |Cite
|
Sign up to set email alerts
|

Who can’t pay for health care?

Abstract: BACKGROUND:In an era of rising health care costs, many Americans experience difficulty paying for needed health care services. With costs expected to continue rising, changes to private insurance plans and public programs aimed at containing costs may have a negative impact on Americans' ability to afford care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 9 publications
3
33
0
3
Order By: Relevance
“…While identification of these factors is of interest in its own right, it is particularly important in the New Zealand context, mainly because ensuring equitable access to services is one of the seven fundamental principles guiding the 2001 New Zealand Health Strategy [7]. Secondly, the bulk of research in this area has been carried out mainly on American data and it is important to examine this issue outside the US to see whether the pattern established there applies elsewhere [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…While identification of these factors is of interest in its own right, it is particularly important in the New Zealand context, mainly because ensuring equitable access to services is one of the seven fundamental principles guiding the 2001 New Zealand Health Strategy [7]. Secondly, the bulk of research in this area has been carried out mainly on American data and it is important to examine this issue outside the US to see whether the pattern established there applies elsewhere [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature points to the increasing burden of out-of-pocket expenditures, even among insured populations. [15][16][17][18][19] Two previous studies of the role of financial constraints in TKA disparities among Medicare FFS beneficiaries leave a confusing picture. Mahomed et al 4 concluded that those "whose income level was low enough to qualify for Medicaid supplementation were much less likely to undergo total knee replacement than individuals who did not receive Medicaid supplementation," whereas Skinner et al 6 saw "little association between socioeconomic status and the rate of TKA."…”
mentioning
confidence: 99%
“…Wirtschaftstheoretische Berechnungen aus Australien gehen von einem 20-prozentigen R ü ckgang des Arzneimittelverbrauchs von Rentnern bei Verdoppelung der Zuzahlung von 2,50 auf 5 Australische Dollar ( $ A) und bei einer Erh ö hung auf 6 $ A sogar von einem R ü ckgang um 34 % aus [14] . Trotz der hohen relativen Steigerung geh ö ren derartige Preise unter australischen Einkommensbedingungen eher in den Bereich der " geringf ü gigen Zuzahlungen " , und dennoch ist der Effekt enorm 18 . Und da Zuzahlungen am st ä rksten und nachhaltigsten auf Medikamente zur Behandlung von Herzkreislauferkrankungen und Bluthochdruck sowie Psychotherapeutika wirken, die Patienten in aller Regel langfristig einnehmen m ü ssen [68] , ist davon auszugehen, dass selbst Eigenbeteiligungen relativ geringen Umfangs relevante Folgen f ü r die Gesundheit einer Bev ö lkerung und negative Auswirkungen auf die gesamten Gesundheitsausgaben verursachen 19 .…”
Section: Fehl-steuerung Der Arzneimittelversorgungunclassified
“…17 Am meisten verbreitet ist die Bitte um Ä rztemuster (39,2 % ), gefolgt von der Einnahme geringerer als der verschriebenen Dosen (23,6 % ), Aussetzen verordneter Arzneimittel (16,3 % ), Verzicht auf andere Bed ü rfnisse (15 % ) und Borgen von Geld f ü r den Medikamentenkauf (12 % ) [46] . 18 Derzeit bestehen in Australien fi xe Zuzahlungen f ü r staatlich anerkannte Arzneimittel, die bestimmten Effi zienz-, Sicherheits-und Qualit ä tskriterien gen ü gen m ü ssen, die pro Packung bei umgerechnet 11,80 US-$ liegen, aber f ü r Personen mit Sozialversicherungsanerkennung (Arbeitslose, Studenten, Arme, Behinderte, etc.) nicht mehr als 1,90 US-$ betragen [78] .…”
Section: Fehl-steuerung Der Arzneimittelversorgungunclassified
See 1 more Smart Citation